(untitled) (Phenomenology, Humanities and Sciences, 2020)
The article presents Heidegger’s phenomenological interpretation of Plato’s allegory of the cave reported in his work The Republic. This is an analysis originally conducted with regard to the methodology used. It proposes to reflect on themes evoked by the allegory as truth, idea, freedom and death, in order to overcome their modern representations in the direction of their original meaning, with the purpose of finding them again in the experience of Greek thought. The study takes up Heidegger’s analysis showing that the movement to access the original experience of the formation of concepts constitutes itself in human freedom of thought and in the task of the philosopher as liberator. Heidegger’s analysis is found in his work Being and Truth. The discussions are supported by the works of its main commentators. The present work indicates that philosophy is, in his own experience, the possibility of freedom, already indicated in Plato’s philosophy.